Analisis dan Kontrol Optimal pada Model Dinamik Penyebaran Virus Zika - Suhud Wahyudi; Nurani Dwi Pangestu; Kamiran (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2023)
Zika is a virus from flaviviridae family and flavivirus genus that spread by Aedes Aegypti mosquito and that can cause serious problem disease such as Guillain Barre Syndrome (GBS) and mikrosefalus. In this paper used spreading dynamic zika virus model that consists of two population and divided to sub population Susceptible humans, sub-population Asymtomatic Infected humans, sub-population Infected humans, sub-population Recovered humans, sub-population Susceptible mosquitoes, and sub-population Infected mosquitoes. The model that anlysis by determine the basic reproduction number, the point of disease free and endemic equilibrium, and the stability of each point of equilibrium. Then, do the optimal control using Pontryagin principle with numerical solution given by Range-Kutta method. The simulation results show the decreasing sub-population of infected humans, asymptomatic infected human, and population of mosquitoes after given controls such using condom, treatment, and using indoor residual spray.